Chicken sisters (The) - Numeroff, Laura (U.S.A : HaperCollins Publishers, 1997)
The chicken sisters drive a troublesome wolf home to his mother with their overwhelming eccentricities.
"A Laura Geringer book."
Keywords: Chickens--Fiction; Sisters--Fiction